Application of quizziz paper mode in learning evaluation increases students' learning enthusiasm - Aldevella, Kamelia; Utami, Ratnasari Diah (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Efforts to improve the quality of learning can leverage advancements in science and technology. The quality of learning by utilizing technological advancements can help educators choose effective teaching strategies. The purpose of this research is to determine: (1) the implementation of Quizizz paper mode in student learning evaluation, (2) the challenges faced by teachers and students in the implementation of Quizizz paper mode in learning evaluation. This research uses a qualitative approach with a descriptive method. Data were collected through observations, interviews, and documentation. The research data sources were obtained using primary data, namely from 10 fifth-grade students and 1 teacher as the fifth-grade teacher at SD N Turunan Andong. This research was conducted from December 2024.The research results show that: (1) the implementation of Quizizz paper mode in learning evaluation helps teachers to increase student learning enthusiasm, thereby influencing their learning outcomes, (2) the challenges of using Quizizz paper mode can be overcome by teachers and students without affecting the ongoing learning, so the learning conditions remain conducive.